Learning by doing, precommitment and infant industry promotion. - Leahy, D; Neary, J (Blackwell Publishing, 1999)
We examine the implications for strategic trade policy of different assumptions about precommitment in a two-period Cournot oligopoly game with learning by doing. The inability of firms and governments to precommit to future actions encourages strategic behaviour which justifies an optimal first-period export tax relative to the profit-shifting benchmark of an export subsidy. In the linear case the optimal subsidy is increasing in the rate of learning with government precommitment but decreasing in it without, in apparent contradiction to the infant-industry argument. Extensions to active foreign policy, distortionary taxation and Bertrand competition are also considered.